Factors Affecting Human Visual Behavior and Preference for Sneakers: An Eye-Tracking Study - Chen, Zihao; Song, Wenfang (Frontiers in Psychology, 2022)
Human visual behavior on a product significantly affects their purchasing behavior during online shopping. Here, two experimental studies were performed to investigate human visual behavior and preference for sneakers using an eye tracking technology. The first study discovered that shoelace and vamp AOIs attracted more attention than other AOIs. The second study explored factors affecting human behavior on sneakers, which employed 30 students from different professional backgrounds (i.e., Fashion major and non-fashion major), and examined 24 sneakers, i.e., combinations of four shoelace styles and six vamp materials. Results showed that both genders irrespective of their professional backgrounds were more concerned about the shoelaces than vamps. The shoelace AOI gained more attention of females than males, while the vamp AOI was more concerned by males than females. The vamp AOI was more concerned by non-professionals than professionals, while the shoelace AOI was paid more attention by professionals than non-professionals. Besides, flat or round shoelaces, and canvas, cow leather or cotton flannel vamp materials were more preferred by participants than other types. The findings are of great help for fashion product designers, manufacturers and sellers to provide the product required by customers.